Jane Eyre’s moral integrity revealed through five essential aspects - Budiarto, Budiarto; Suhendar, Suhendar (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
This article explores the moral integrity of Jane Eyre, the main character in Charlotte Brontë’s novel Jane Eyre, using a qualitative descriptive method focused on textual analysis. The study aims to understand how Jane's internal motivations, emotions, beliefs, goals, and actions represent a consistent and principled moral identity. Selected scenes and dialogues from the novel were analyzed, particularly those in which Jane faces emotional and ethical conflicts, such as her interactions with Mr. Brocklehurst, Mr. Rochester, and St. John Rivers. The analysis focuses on five aspects of moral integrity: staying true to personal values, emotional honesty, resistance to outside pressures, moral courage, and consistency between belief and behavior. The data were examined using interpretive tools from psychology, linguistics, and literary studies. Self-Determination Theory (Deci & Ryan, 2000), Blasi’s Theory of Moral Identity (1984), and Speech Act Theory (Austin, 1962; Searle, 1979) provided the theoretical foundation for this study. The findings reveal that Jane consistently shows moral strength by refusing to act against her values, even in situations involving love, authority, or comfort. Her integrity is reflected in the way she speaks, thinks, and acts, showing growth from childhood to adulthood. This study contributes to the fields of literature, psychology, and education by offering a clear framework for analyzing character-based moral development. It is useful for educators teaching ethics through literature and for researchers interested in interdisciplinary approaches to character analysis. The article provides a model for examining moral identity in literary texts using psychological and linguistic theories.